Methanogenesis in sediments of a tropical coastal wetland: a culture-dependent method - Torres-Alvarado, María del Rocío (2024)
Introduction: Methanogenic archaea (MA), participate in the anaerobic mineralization of organic matter in mangrove sediments, their activity is related to atmospheric warming due to the production of methane; several environmental variables can influence the presence of MA and methane production in these sediments. Objective: To analyze, through culture-dependent techniques, viable methanogenic archaea (VMA) in the sediments, and the production of methane from acetate in different climatic periods in the mangrove El Morro-La Mancha, Veracruz, Gulf of Mexico. Methods: From May to November 2019, following a salinity transect, sediment samples from El Morro-La Mancha mangrove were collected at three locations, in three different climatic seasons, dry (May), rainy (October) and northern (November) (N = 9). VMA in the sediments was quantified using the Most Probable Number (MPN) technique with acetate and methanol as substrates. The influence of sulfate on methane production was analyzed from acetate in microcosm by gas chromatography and the chemical variables of salinity, pH, Eh, carbohydrates, organic content, and carbonates in the sediments were evaluated. Results: The abundance of VMA was 102 to 108 MPN/g of wet sediment, higher than that reported in other studies, this abundance was higher when methanol (104-108 MPN/g sediment) was used as substrate, compared to acetate (102-105 MPN/g sediment); methane production in the microcosms increased in sulfate-free conditions (29.78-929.75 nmol CH4/month) and in the sediments of the rainy season. Conclusion: The influence of the chemical conditions of the mangrove sediments on the methanogenic dynamics is highlighted, determining that in the rainy season, the decrease in salinity, more electronegative Eh, and the increase in organic fractions favored the methanogenesis. Objetive: To analyze, through culture-dependent techniques, the abundance of MA and the production of methane in different climatic periods in the mangrove El Morro-La Mancha, Veracruz, Gulf of Mexico. Methods:  From May to November 2019, following a salinity transect, sediment samples from El Morro-La Mancha mangrove were collected at three sampling locations, in three different climatic seasons, dry (May), rainy (October) and northern (November) (n=9). The methanogenic abundance in the sediments was quantified using the Most Probable Number (MPN) technique with acetate and methanol as substrates; methane production was analyzed from acetate by gas chromatography and the chemical variables of salinity, pH, Eh, carbohydrates, organic content and carbonates in the sediments were evaluated. Results: The abundance of MA was 102 to 108 cells/g of wet sediment, higher to that reported in other studies, this abundance was higher when methanol (104 - 108 cells/g sediment) was used as substrate, compared to acetate (102 - 105 cells/sediment); methane production increased in rains with 13% compared to dry. Conclusion: Highlighted the influence of the chemical conditions of the mangrove sediments on the methanogenic dynamics, determining that in the rainy season, the decrease in salinity, Eh more electronegative and the increase in organic fractions favored both methanogenic abundance as methane production.